Effect of TiO2 Nanoparticles on Physical and Mechanical Properties of Cement at Low Temperatures - Li Wang; Hongliang Zhang; Yang Gao (Advances in Materials Science and Engineering)
Low temperature negatively affects the engineering performance of cementitious materials and hinders the construction productivity. Previous studies have already demonstrated that TiO2 nanoparticles can accelerate cement hydration and enhance the strength development of cementitious materials at room temperature. However, the performance of cementitious materials containing TiO2 nanoparticles at low temperatures is still unknown. In this study, specimens were prepared through the replacement of cement with 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, and 5 wt.% TiO2 nanoparticles and cured under temperatures of 0°C, 5°C, 10°C, and 20°C for specific ages. Physical and mechanical properties of the specimens were evaluated through the setting time test, compressive strength test, flexural strength test, hydration degree test, mercury intrusion porosimetry (MIP), X-ray diffraction (XRD) analysis, thermal gravimetric analysis (TGA), and scanning electron microscopy (SEM) in order to examine the performance of cementitious materials with and without TiO2 nanoparticles at various curing temperatures. It was found that low temperature delayed the process of cement hydration while TiO2 nanoparticles had a positive effect on accelerating the cement hydration and reducing the setting time in terms of the results of the setting time test, hydration degree test, and strength test, and the specimen with the addition of 2 wt.% TiO2 nanoparticles showed the superior performance. Refined pore structure in the MIP tests, more mass loss of CH in TGA, intense peak appearance associated with the hydration products in XRD analysis, and denser microstructure in SEM demonstrated that the specimen with 2 wt.% TiO2 nanoparticles exhibited preferable physical and mechanical properties compared with that without TiO2 nanoparticles under various curing temperatures.